Two Kinds of Reasoning - Rips, Lance J. (Psychological Science, 2001)
According to one view of reasoning, people can evaluate arguments in at least two qualitatively different ways: in terms of their deductive correctness and in terms of their inductive strength. According to a second view, assessments of both correctness and strength are a function of an argument's position on a single psychological continuum (e.g., subjective conditional probability). A deductively correct argument is one with the maximum value on this continuum; a strong argument is one with a high value. The present experiment tested these theories by asking participants to evaluate the same set of arguments for correctness and strength. The results produced an interaction between type of argument and instructions: In some conditions, participants judged one argument deductively correct more often than a second, but judged the second argument inductively strong more often than the first. This finding supports the view that people have distinct ways to evaluate arguments.